DENV-captured plasmin enhances mosquito midgut infection and is inhibited by an endogenous Kazal-type inhibitor AaTI. Issue 10 (20th December 2019) - Mok, Yu Keung; Ramesh, Karthik; Wong, Benjamin; Sayed, Ahmed; Misse, Dorothee; Manjanatha, Kini; Pompoon, Julien
Abstract : Deciphering how dengue pathogenesis influences vector transmission will improve our understanding on virulence evolution, epidemiology and design of transmission-blocking tools. Here, we demonstrate that addition to blood meal of plasmin, the human fibrinolytic factor, increased permeability and DENV infectivity in mosquito midgut, resulting in higher infection rate and dissemination in whole mosquitoes. Further, we show that a plasmin-selective mosquito Kazal-type protease inhibitor, AaTI reverted this enhanced infection by inhibiting proteolysis. We also determined that DENV or E-protein, plasmin (not plasminogen) and AaTI can interact to form a tripartite complex using biolayer interferometry, suggesting physical interaction between DENV E-protein and kringle domain of plasmin. Our study suggests that (a) DENV recruit plasmin in solution to increase local proteolytic activity in midgut, thus enhancing DENV infection and (b) AaTI can act as a transmission-blocking agent, which could also alleviate hemorrhagic patients. By discovering that dengue pathogenesis can enhance DENV fitness by increasing mosquito infectivity, our results provide the first evidence of mosquito-based evolutionary pressures on dengue virulence in human. We are currently determining the effect of plasmin and AaTI on DENV infection in cellular and mouse models. H/D exchange mass spectrometry is being employed to identify which kringle domain of plasmin is interacting with DENV E-protein. The structure of the complex formed between the kringle domain of plasmin and DENV E-protein and between the catalytic domain of plasmin and AaTI are in progress.